(3MGTjI eYGde GdOjfs - (3GdMSjfj, GdeQYTj, GdBedj, GdGUagGfj, NdjaI SdWGf, YdGA GdOjf, MSjf Hf eMeO Hf eMehO, J (B1064 (3g`s ((3YHO Gddg Hf eMeO MSfs)
(3ChdgG (B:s
(3GdMeO ddg (B... (3Efj bO cJHJ Mjf eWGdYI cJGH GdeYGde GdOjf ef eUfaGJ Rjf GdOjf GdYGedj HYV GdMhGTj Ydjg bGUOG JhVjM ebGUOg hJcKjQ ahGFOg HebOGQ GdhSY hGdWGbI hJLfHfG Yf GdGWfGH hGdEWGdI (B..s
(3BNQgG (B:s
.. (3dG jNai Cf GMJeGd GdJChjd eSJQc EP GdaQV JSGhjgeG aj LejY GdCehQ Shi eNGdaI GdYGeI hehGabJgG aGMJeGd GdJbjI aj CMOgeG Ohf GdBNQ jhLH GdJQLjM aeG PcQg SGbW (B.s
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf (B1\641s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
Keywords: (3CUhd Gdabgs